Pembinaan dan Pengembangan Literasi Kesastraan di Sekolah - Yulia Sari, Mira; Beri Ledang, Herlince; Bagus Putrayasa, Ida; Anfal, Wahyuddin; Nofriyanti Manu, Ferderika; Afni, Nur; Sudiana, I Nyoman (Universitas Tidar, 2024)
Literary literacy in schools was essential because it had a positive impact on both the academic and personal development of students, such as enhancing critical thinking skills. Students learnt to analyze plot, characters, and themes, as well as evaluated various perspectives and meanings within texts. Literary literacy also enriched vocabulary and language skills. Reading various literary genres expanded students' vocabulary and improved their ability to understand and use language effectively. The aimed of this study was to understand how literary literacy fostered and developeded in schools. This research used a literature study method with a narrative review model. In this narrative review, data from several journals were analyzed and summarized based on the author's experience. The study employed a qualitative method with secondary data obtained from relevant journals. The researchers used a descriptive analytical method, collecting, identifying, organizing, and analyzing various data found. The results of the study showed that the development and enhancement of literary literacy in schools in Indonesia include: 1) Intensive Reading Programs within the GLS program, 2) Use of Technology, 3) Interactive Teaching Methods, 4) Teacher Training and Professional Development, and 5) Improvement of School Libraries.